DECISION SUPPORT SYSTEM PEMBUKAAN LOKASI BARU JASA SERVIS MOTOR BERBASIS PROFILE MATCHING - Nuryanto, Imam; Setiawan, Aries; Farida, Ida; Wibowo, Sasono; Widjajanto, Budi; Prihandono, Adi (Jurusan Teknologi Informasi Universitas Semarang, 2024)
As the volume of motorbikes increases, the number of motorbike service outlets also increases. However, not all service places get customers equally, from the customer's side various variables really determine visits such as location, level of spare parts availability, level of service to consumers and price. Likewise, in terms of service owners, when opening a new service location, they need to pay attention to various variables such as proximity to residential areas, number of competitors, capacity of passing vehicles, and proximity to spare parts suppliers. To collaborate several influential variables to produce a decision regarding the right place, a method is needed that is capable of carrying out calculations to produce a ranking of locations that will have an influence. One method that can be offered is profile matching. This method performs by finding the difference between the weight value determined at the beginning and the input value for each location object. The ranking results of all location objects can be used as alternative locations for appropriate service locations..